2020
DOI: 10.1515/opag-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of crop farmers coping strategies to pastoralism/nomad activities in Nigeria

Abstract: AbstractThis study examined the coping strategies of crop farmers to pastoralist activities in Odo-Otin Local Government Area of Osun State, Nigeria. A multistage sampling technique was used to select 120 farmers. The data were collected using a well-structured questionnaire and interview and were analysed using descriptive and inferential statistical tools. The result revealed various levels of damage caused to food security by the pastoralist as follows: compaction of soil (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 9 publications
10
7
1
Order By: Relevance
“…Information presented in Table 3 shows that loss of This is evident in the tremendous price hike of food commodities across the country. This is similar to the finding of Alao et al (2019) and Obaniyi et al (2020) who argued that the conflict has continued to reduce the quantity of farmers' output and loss of income due to the destruction of crops by cattle herders. Other effects of conflicts on farmers include insecurity/loss of community peace (mean = 1.45), displacement of farmers and families (mean = 1.42), and acquisition of weapons to defend themselves (mean = 1.39).…”
Section: Effects Of Farmer-herder Conflictsupporting
confidence: 90%
See 2 more Smart Citations
“…Information presented in Table 3 shows that loss of This is evident in the tremendous price hike of food commodities across the country. This is similar to the finding of Alao et al (2019) and Obaniyi et al (2020) who argued that the conflict has continued to reduce the quantity of farmers' output and loss of income due to the destruction of crops by cattle herders. Other effects of conflicts on farmers include insecurity/loss of community peace (mean = 1.45), displacement of farmers and families (mean = 1.42), and acquisition of weapons to defend themselves (mean = 1.39).…”
Section: Effects Of Farmer-herder Conflictsupporting
confidence: 90%
“…It has posed much of serious negative implications for Nigeria's national integration; and has also heightened the level of insecurity and food shortage. The economic effects of these conflicts have led to a loss of lives, displacement of farmers, loss of production, loss of houses and property, infrastructural damage, and scarcity of agricultural products among others (Alao et al, 2019;Obaniyi et al, 2020;Mercy Corps, 2015;Bello, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidences have shown that this situation is common in the northern part of Nigeria but the southern states have also started experiencing this menace by the Fulani herdsmen (Bello, 2013;Ikhuoso e al., 2020;Kazzah, 2018;Salihu, 2018). This finding is supported by Obaniyi et al (2020) who identified damages done to crop farmers in Osun State by the Fulani herdsmen attacks.…”
Section: Research Implicationmentioning
confidence: 65%
“…Considering the myriad of problems confronting crop farmers in Nigeria, empirical studies have documented the spate of wanton destruction of crops on farmers' farmland by Fulani herdsmen's cattle.This has become a common phenomenon in the Northern (north-east, north-west and north-central) part of Nigeria (Bello, 2013;Ikhuoso et al, 2020;Salihu, 2018). In recent time, apart from already identified problems such as lack of credit, inadequate farm inputs, inadequate market information and lack of rural infrastructure, crop farmers in the South-west Nigeria now experience similar attacks by the Fulani herdsmen (Obaniyi et al, 2020). While in search for pasture and water for their cattle, herders directed their cattle to crop farmers' farm and the cattle were made to feed on the growing crops and in the process, destroying the crops (such as cassava).…”
Section: Introductionmentioning
confidence: 99%